Between Faith and Fandom: Hijabi Women Engaging with Queer Manhwa in Digital Media - Mulia, Yasmin; Safitri, Reza (Alphabet, 2026)
This study investigates how hijabi Muslim women’s engagement with queer manhwa is constructed, contested, and negotiated within contemporary social media discourse. The research examines public conversations across platform to explore how digital publics interpret the convergence of Islamic piety and participation in queer fandom cultures. Existing studies digital fandom and media consumption largely center on Western, secular audiences, leaving limitd attention to how religious identitites shape interpretive practices in non-Western contexts. Research on Muslim womenin digital spaces often emphasizes piety, modesty, or representation, but rarely examines their engagement with taboo or queer media as a site of moral negotiation. Consequently, there is a gap in understanding how hijabi women actively reconcile faith, affect, and fandom through everyday digital practices, particularly in the context of queer manhwa consumption. Through Moustakas’ lense of phenomenology that emphasized each individual’s experience, findings reveal a polarized discursive landscape in which hijabi readers are simultaneously policed for violating moral norms and defended as autonomous media consumers capable of complex interpretation. These debates illuminate how social media functions as a moral arena where notions of modesty, desire, cultural authenticity, and religious identity are actively negotiated. Rather than framing hijabi women’s engagement with queer manhwa as a contradiction, the discourses reveal dynamic processes of identity negotiation, boundary management, and affective participation shaped by both religious frameworks and digital affordances. This study contributes to broader discussions on gender, faith, digital fandom, and the changing face of Muslim womanhood in the era of globalized popular culture.